Confirmatory factor analysis and validation of a statistical literacy instrument for elementary school students - Naely Nishfani Mz; Ani Rusilowati; Multazam Multazam (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2026)
Despite the fact that statistical literacy is an essential skill for students and should be acquired at an early age, there is still limited progress in the development of statistical literacy instruments for elementary schools. This study aimed to develop and validate an instrument for assessing statistical literacy based on the Asesmen Kompetensi Minimum (AKM) model for elementary school students. The research sample consisted of 200 fifth-grade elementary school students. Construct validity was examined using Confirmatory Factor Analysis (CFA) to test the suitability of the indicators used in the statistical literacy instrument. The indicators were adapted from the frameworks proposed by Garfield and PARIS21. CFA was conducted using the Jamovi software. The results indicate that the overall model demonstrates a good fit, confirming that the theoretical indicator structure is empirically supported. However, there are several items with low or insignificant factor loadings that need to be revised or eliminated to improve the quality of the instrument. These findings highlight the importance of item refinement in developing a valid and reliable AKM-based statistical literacy assessment. This study contributes new insights by providing a validated instrument for measuring elementary school students’ statistical literacy.